On the effects of selective below-cost pricing in a vertical differentiation model - Stefano Colombo (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We analyse the effects of predation in a vertical differentiation model, where the high-quality incumbent is able to price discriminate while the low-quality entrant sets a uniform price. The incumbent may act as a predator, that is, it may price below its marginal costs on a subset of consumers to induce the rival's exit. We show that the entrant may adopt an aggressive attitude to make predation unprofitable for the incumbent. In this case predation does not occur and the equilibrium prices are lower than the equilibrium prices which would emerge in a contest of explicitly forbidden predation. Moreover, we show that when the incumbent may choose whether to price discriminate or not before the game starts, if the quality cost function is sufficiently convex, there always exists a parameter space on which the incumbent prefers to commit not to price discriminate.
Keywords: D43; L12; L41; 330; Vertical differentiation; selective below-cost pricing; predation; price discrimination; Niedrigpreisstrategie; Produktdifferenzierung; Produktqualität; Verdrängungswettbewerb; Oligopol; Theorie